Agresia pacientov voči sestrám na psychiatrických pracoviskách - Dimunová, Lucia; Žemličková, Alžbeta (Ošetrovateľstvo, 2019)
Aim: To determine the incidence rate of forms of inpatient aggression towards nurses. Methodology and sample: Data collection was implemented by means of the self-assessment scale: Violence and Aggression of Patients Scale (VAPS). The sample comprised 219 nurses, who working on psychiatric wards in Slovakia. Results: Of the total sample, 97.2 % of nurses had personal experience of various forms of aggression over the past year of their profession. Most often, nurses reported the frequency of verbal attacks by patients (96.8%). 83.1 % of nurses reported physical aggression without the use of assault weapons. 22.8 % of nurses declared aggression with the use of assault weapons and contact forms of sexual aggression. The relationship between experience of patient aggression and level of education was not proved to be significant. Conclusion: The incidence of patient aggression towards nurses is a significant risk factor for nurses’ working environments, which should continue to be addressed.
Keywords: Aggression; ošetřovatelství v psychiatrii; lidé; průzkumy a dotazníky; agrese; Nurses; Inpatients; hospitalizovaní pacienti; Surveys and Questionnaires; duševně nemocní; Persons with Psychiatric Disorders; Psychiatric Department, Hospital; psychiatrické oddělení nemocnice; zdravotní sestry; Psychiatric Nursing; Humans